HUBUNGAN SIKAP DAN PENGERTAHUAN IBU TENTANG KEBERSIHAN GIGI DAN MULUT DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA 3 – 5 TAHUN DI DESA SEI KEPAYANG TENGAH KABUPATEN ASAHAN TAHUN 2016 - Budiyanthy, Donna (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2019)
Dental caries is a dental tissue disease characterized by tissue damage, starting from the surface of the tooth and the inter area extending towards the pulp. Parents do not care about the habit of brushing their teeth, if a child does not want to brush their teeth so parents should be able to force their children to brush their teeth, especially when going to bed at night. Based on temporary observations there were 6 children who had carious teeth saying that they rarely brushed their teeth, as well as varied education levels of their parents. This study aims to determine the relationship between attitudes and knowledge of mothers about dental and oral hygiene with the incidence of caries in 3-5 year olds in Sei Kepayang Tengah Village, Asahan Regency. The type of research is analytic with cross sectional design. The population in this study was the mother of Sei Kepayang Tengah Village in Asahan Regency and a sample of 57 people, the sampling technique was purposive sampling, the method of collecting data by interviewing indirectly using a questionnaire sheet. Analysis of data using chi-square then there is a relationship between attitude (p = 0.033) and knowledge (p = 0.001) of mothers regarding dental and oral hygiene with the incidence of caries in children aged 3-5 years. To be expected for health workers who play a very important role in increasing the knowledge of mothers need to conduct health education about dental and oral health regarding how to teach correct tooth brushing to children, the right time to brush teeth, good food for tooth extraction, action when teeth children are sick, do the cutting on hollow teeth, it is recommended to do routine checks every 6 months.